Match and training loads of professional soccer players in relation to their tactical position - Ispyrlidis, I.; Gourgoulis, V.; Mantzouranis, N.; Gioftsidou, A.; Athanailidis, I. (Journal of Physical Education and Sport, 2020)
The aim of this study was to compare the internal and external loads of professional soccer players in relation to their tactical position during the in-season trainings and matches. 13 players from one team of the Super League 2 (2nd Greek Division), aged 26±4.6yrs, with body mass of 77.4±6.96kg, stature 181±50cm and body fat 8.7±1.51%, participated in the current study. The players' loads were recorded in three trainings per microcycle and during the team's official matches in a 6-week period by the use of a Polar Team Pro tracking system (©Polar Electro, Sports instruments, Kempele, Finland. Repeated measures analysis of variance along with the Bonferroni multiple comparisons was used for the statistical treatment of the data. Independently from their tactical position, the players spent significantly more time with low heart rate during trainings, while they spent significantly more time with high heart rate in matches. However, the fullbacks, the central midfielders and the central defenders performed with high heart rates, in comparison with the other players' positions, in both trainings and matches (p<0.05). The distances covered by the players with low running speeds were significantly longer in training(p<0,05), than in matches, while the distances covered with higher running speeds were not significantly different between training and match in all players(p<0,05). Moreover, the covered distances with high running speed did not significantly differ in the studied players according to their tactical positions (p<0,05). Regarding the number of accelerations/decelerations significant greater amounts were detected during trainings, rather than in the official matches in all recorded intensity zones while significant differences in the number of accelerations/decelerations were observed in all players' positions (p<0,05). This study finding suggest that the coaches must simulate the high intensities of the match during the competitive microcycles trainings adapting the physical conditioning training in relation to the players' tactical position.